A STOCHASTIC PROGRAMMING APPROACH TO LIQUIFIED NATURAL GAS PLANNING - Moraes,Leonardo A.M. (2016)
ABSTRACT This work reports on modeling and numerical experience in solving the liquefied natural gas (LNG) planning for an oil and gas company. We developed a model to optimize said purchase, optimizing the amount of LNG bought on the spot and on the long-term markets, based on the predicted demand for the planning horizon. A stochastic approach to address uncertainties related to the LNG demand and spot prices is presented. The expected cost of the operation is minimized, considering stock costs and the possibility to export the surplus gas. Numerical experiments in a real-life case are assessed.